1989
DOI: 10.1080/02724936.1989.11748619
|View full text |Cite
|
Sign up to set email alerts
|

Oral refeeding following acute gastro-enteritis: a clinical trial using four refeeding regimes

Abstract: A clinical trial using four different oral refeeding regimes was conducted in 100 patients following acute gastro-enteritis. There was no difference in terms of the diarrhoea-relapse rates among the four groups of patients. However, a better weight gain was recorded in the groups using a lactose-free soy formula and a low-lactose low-fat cow's milk formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This practice was derived from the observation that stooling is increased immediately after a feeding. Recently, a number of studies in developing and developed countries have shown that the duration and nutritional impact of acute gastroenteritis is reduced by offering a reasonable age appropriate diet as soon as rehydration is complete (Hjelt et al, 1989;Quak et al, 1989). Breastfed infants are nursed throughout the rehydration period.…”
Section: Rehydrationmentioning
confidence: 99%
“…This practice was derived from the observation that stooling is increased immediately after a feeding. Recently, a number of studies in developing and developed countries have shown that the duration and nutritional impact of acute gastroenteritis is reduced by offering a reasonable age appropriate diet as soon as rehydration is complete (Hjelt et al, 1989;Quak et al, 1989). Breastfed infants are nursed throughout the rehydration period.…”
Section: Rehydrationmentioning
confidence: 99%
“…The average duration of hospitalization was not significantly different between the 2 groups. Quak et al (6) assessed the use of soy formulas during refeeding after acute gastroenteritis. They noted that the 25 pediatric patients fed with full-strength soy formulas recovered more rapidly and gained weight, whereas those fed with cow-milk formulas had more relapses of watery diarrhea.…”
Section: Use Of Soy In Lactose Intolerancementioning
confidence: 99%